1999
DOI: 10.1091/mbc.10.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rab25 and Rab11a with the Apical Recycling System of Polarized Madin–Darby Canine Kidney Cells

Abstract: Recent evidence suggests that apical and basolateral endocytic pathways in epithelia converge in an apically located, pericentriolar endosomal compartment termed the apical recycling endosome. In this compartment, apically and basolaterally internalized membrane constituents are thought to be sorted for recycling back to their site of origin or for transcytosis to the opposite plasma membrane domain. We report here that in the epithelial cell line Madin-Darby Canine Kidney (MDCK), antibodies to Rab11a label an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
343
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(382 citation statements)
references
References 51 publications
37
343
1
1
Order By: Relevance
“…As described, AREs are enriched with transcytotic dIgA (Apodaca et al, 1994) and Rab 25 (Casanova et al, 1999), but are relatively depleted of Tfn (Apodaca et al, 1994). Results presented in Figure 8, A and B, fulfilled these criteria, hence suggesting that Cav1-positive organelles are either linked or reside in proximity to AREs (Bush et al, 2006).…”
Section: Cav1 Codistributes With Diga-pigr and Rab25-positive Clustersupporting
confidence: 64%
“…As described, AREs are enriched with transcytotic dIgA (Apodaca et al, 1994) and Rab 25 (Casanova et al, 1999), but are relatively depleted of Tfn (Apodaca et al, 1994). Results presented in Figure 8, A and B, fulfilled these criteria, hence suggesting that Cav1-positive organelles are either linked or reside in proximity to AREs (Bush et al, 2006).…”
Section: Cav1 Codistributes With Diga-pigr and Rab25-positive Clustersupporting
confidence: 64%
“…Figure 3C, 2-5). The ARE was visualized using an antibody raised against rab11a, a well-established ARE-associated small GTPase (Casanova et al, 1999;Brown et al, 2000;Leung et al, 2000;Prekeris et al, 2000). In parental HepG2 cells, rab11a labeling was exclusively subapical, as expected (Figure 4, F and G).…”
supporting
confidence: 72%
“…These data suggest that expression of the AKAP-IS peptide and concomitant reduction of centrosome-associated PKA-RII␣ interferes with the subapical positioning of the centrosome and the orientation of a major part of the microtubule net- work in a manner that seems unrelated to the enzymatic activity of PKA. Several endosomal compartments such as the CE/SAC and the rab11a-positive ARE are typically concentrated around the centrosome in epithelial cells (Casanova et al, 1999;Leung et al, 2000;Hobdy-Henderson et al, 2003), and they mediate the transcellular flow of membranes (for review, see Hoekstra et al, 2004), a process that has been shown to be stimulated by OSM (van der Wouden et al, 2002). Therefore, we next examined the subcellular position of the CE/SAC and ARE in control HepG2 cells and HepG2 cells expressing the AKAP-IS peptide.…”
mentioning
confidence: 99%
“…This compartment was enriched in TfR and did not contain EEA1, a marker of early sorting endosomes (Wilson et al, 2000), or Rab11, a marker of AREs in MDCK cells (Casanova et al, 1999;Wang et al, 2001; Figure 2A). All of these characteristics are typical of a compartment denominated common RE, involved in the recycling of TfR and LDLR to the basolateral membrane and in the transcytosis of Polymeric IgA Receptor to the apical membrane via ARE (Futter et al, 1998;Brown et al, 2000;Wang et al, 2000).…”
Section: Tgn-vs Ap1b-mediated Sorting Pathwaysmentioning
confidence: 99%